2023
DOI: 10.1002/cbdv.202300654
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Phytochemical Content by LC/MS/MS and Anticholinergic, Antiglaucoma, Antiepilepsy, and Antioxidant Activity of Apilarnil (Drone Larvae)

Hakan Inci,
Ebubekir Izol,
Mustafa Abdullah Yilmaz
et al.

Abstract: Apilarnil is 3‐7 days old drone larvae. It is an organic bee product known to be rich in protein. In this study, the biological activities of Apilarnil were determined by its antioxidant and enzyme inhibition effects. Antioxidant activities were determined by Fe3+, Cu2+, Fe3+‐TPTZ ((2,4,6‐tris(2‐pyridyl)‐s‐triazine), reducing ability and 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH•) scavenging assays. Also, its enzyme inhibition effects were tested against carbonic anhydrase I and II isoenzymes (hCA I, hCA II), acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In addition, the type of glucaric acid could be thought as Glu instead of a group of this kind of acid that produced a DPI of 209 Da, then losing H 2 O to formalize 191 Da. Compounds 11, 15 and 21 with same fundamental skeleton of C 15 H 16 O 11 possessed a DPI at 209 Da by the NL of C 9 H 6 O 3 (162 Da), and were definitively identified as caffeoylglucaric acid and its isomers by matching with references and the literature (Inci et al, 2023; Li, Sun, et al, 2021) (Figure S1C).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, the type of glucaric acid could be thought as Glu instead of a group of this kind of acid that produced a DPI of 209 Da, then losing H 2 O to formalize 191 Da. Compounds 11, 15 and 21 with same fundamental skeleton of C 15 H 16 O 11 possessed a DPI at 209 Da by the NL of C 9 H 6 O 3 (162 Da), and were definitively identified as caffeoylglucaric acid and its isomers by matching with references and the literature (Inci et al, 2023; Li, Sun, et al, 2021) (Figure S1C).…”
Section: Resultsmentioning
confidence: 66%
“…The amounts of 45 organic acids were found in BCAVA using the strategic structures of DPIs and NL. In Figure 1 (Inci et al, 2023;Li, Sun, et al, 2021) (Figure S1C). 3.5 | Quantification analysis of BCAVA from different origins…”
Section: Identification Of Organic Acidsmentioning
confidence: 99%
“…Additionally, apilarnil contains unsaturated fatty acids in both free and bound forms, unique decenoic acids, and some hydrophobic phenolic compounds that are 15-30 times more effective at neutralizing free radicals. [94] Drone brood's capacity to lower oxidative stress is significantly aided by flavonoids and other phenolic substances. [13,17] Apilarnil has high levels of antioxidants and is sometimes referred to as the male version of royal jelly.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Koşum et al (2022), analysing the phenolic/organic acid profile, observed that trans-aconitic acid (11.20 ± 0.32 µg/g) and fumaric acid (5.03 ± 0.41 µg/g) represented the significant compounds [72]. Inci et al (2023) showed that the highest compound concentrations, expressed as mg analyte/g dry extract, were represented by quinic acid (1091.04), fumaric acid (48.714), kaempferol (39.946), and quercetin (27.508) [73]. In contrast, in the present study, it could be observed that ferulic acid had the highest amount, 126.36 µg/g, followed by epicatechin with a concentration of 74.03 ± 1.85 µg/g.…”
Section: Individual Polyphenols Content Detected By Lc-msmentioning
confidence: 99%